AGE-DEPENDENT INDEXES OF IMMUNITY IN THE PATIENTS WITH PSORIATIC ARTHRITIS - A. A. Barilo (SPb RAACI, 2019)
Psoriatic arthritis is a chronic progressive systemic inflammatory disease of joints and spine, which leads to the development of erosive arthritis, bone resorbtion, multiple enthesitis and spondylitis. Severe clinical course, resistance to therapy, high prevalence of disability, increased mortality of patients determine a need for further study of the disease. Psoriatic arthritis is a multifactorial disease including immune pathogenic factors representing a complex process of interaction between cellular and humoral components of immune system. The most important way of activating epidermal cells and synovial membrane proliferation in psoriatic arthritis is an imbalance of proinflammatory and anti-inflammatory cytokines. It is noted that the features of clinical course in psoriasis are age-dependent. The study of immune response indices in different age groups allows to reveal distinct progression features of the psoriatic pathology.The purpose of this study was to compare concentrations of proinflammatory and anti-inflammatory cytokines, cellular and humoral immunity, and to conduct a comparative analysis in young and adult patients with psoriatic arthritis.The study included a group of patients with psoriatic arthritis (n = 101) who were divided by their age: group 1, from 18 to 44 years (n = 43); group 2, over 44 years (n = 58). The control groups (3 and 4) included virtually healthy people (n = 103) matched for sex and age with the patients. Populational and subpopulation profiling of blood lymphocytes was performed by flow-cytometry using monoclonal antibodies to CD3, CD4, CD8, CD16, CD19 (LLC “Sorbent”, Moscow, Russia). Phagocytic activity of peripheral blood neutrophils was assessed microscopically by uptake of latex particles. Concentrations of IgA, IgM, and IgG immunoglobulins, circulating immune complexes, cytokines (IL-4, IL-6, IL-10, TNFα) in blood serum was determined by enzyme-linked immunosorbent assay. Statistical evaluation of the results obtained was performed using applied “Statistica 6.0” software.In all the age subgroups of patients with psoriatic arthritis, we have revealedstatistically significant differences against controls, i.e., increased relative and absolute number of CD3-CD16+ lymphocytes in peripheral blood, higher concentration of CIC-C1q, with decreased concentrations of IgA, IgM, IgG in blood serum. The analysis of the main cellular and humoral indicators of immunity in psoriatic arthritis patients revealed a statistically significant differences for psoriatic arthritis in young and adulthood. E.g., the serum concentration of IL- 10 was statistically significantly lower in psoriatic arthritis at a young age in comparison with adult psoriatic arthritis. Phagocytic number and IgG concentration in serum were statistically significantly lower in adults with psoriatic arthritis adulthood than in young patients.In conclusion, The revealed changes in immunological indices in psoriatic arthritis in young and adult patients indicate to differences against healthy controls, as well as intergroup differences. Previous studies have not revealed statistically any significant differences in immunological parameters between young and adult patients with psoriatic arthritis in, thus suggesting a presence of immune disorders associated with psoriatic pathology, but not with the age of patients. However, changes of immunological reactivity are observed with increasing age of patients with psoriatic arthritis and development of severe clinical forms, and they can be considered as markers of psoriatic disease progression, such as increased concentrations of IL-10 and lower IgG amounts in blood serum, a decreased phagocytic number.